Corporate transparency and firm value: evidence from sri lanka - Rajakulanajagam, N.; Nimalathasan, B. (University of Jaffna, 2020)
The aim of this study is to investigate the impact of corporate transparency and firm value. Although managers are getting allowances to disclosure more, existing literature reveal that the disclosure brings negative effects and additional cost. However, being transparent is better way to boost up investors’ confidence through that firms could enhance their value. To clear out these conflicts current study empirically investigates the problem using three proxies of firm value such as return on equity, modified Tobin’s Q and share price. Corporate transparency were measured based on the adjusted S&P disclosure and transparency items under three aspects namely, financial transparency and information disclosure, board and management structure and processes and ownership structure and investor rights. The study considered all the listed firm in Colombo stock exchange as the population and after the careful elimination, total of 126 Sri Lankan listed companies were selected to the empirical analysis. Hypotheses of the study were tested based on the multiple regression. The result of the study reveal that the corporate transparency positively influence on firms’ value in Sri Lankan setting. This result could be practicable by disclosing more information voluntarily. This study contributes to the existing literature by examining the corporate transparency through modified disclosure index.
Keywords: Colombo stock exchange; Corporate transparency; Modified tobin’s Q; Share price